Direct‐acting antivirals reduce the risk of tumour progression of hepatocellular carcinoma after curative treatment. Issue 1 (4th November 2021) - Ikenaga, Hiroko; Uchida‐Kobayashi, Sawako; Tamori, Akihiro; Odagiri, Naoshi; Yoshida, Kanako; Kotani, Kohei; Motoyama, Hiroyuki; Kozuka, Ritsuzo; Kawamura, Etsushi; Hagihara, Atsushi; Fujii, Hideki; Enomoto, Masaru; et al.
Abstract: Hepatocellular carcinoma (HCC) has high recurrence rates. HCC sometimes progresses from early‐stage HCC (Barcelona Clinic Liver Cancer [BCLC] stage 0/A) to advanced‐stage HCC after repeated recurrences and treatments. HCC progression deteriorates quality of life and prognosis. However, the effect of direct‐acting antiviral (DAA)‐induced sustained virologic response (SVR) on HCC progression remains uninvestigated. We conducted a retrospective cohort study of patients with hepatitis C virus‐related HCC with BCLC stage 0/A diagnosed for the first time and treated by curative resection or ablation. Using a time‐varying method, we estimated the risk of tumour progression (defined as progression to BCLC stage B‐D) and liver‐related death and the characteristics of repeated recurrence. Overall, 165 patients were enrolled. Following curative HCC treatment, 72 patients received DAA therapy (DAA‐treated group), whereas 93 did not (untreated group). Approximately 75% of the recurrences were at an early stage and expected to be disease‐free by retreatment. We recorded 56 tumour progressions, of which 60.7% were observed after second recurrence. Multivariate adjusted time‐varying Cox regression analysis showed that the DAA‐induced SVR significantly reduced the risk of tumour progression (hazard ratio [HR] 0.28; p  = .001) and liver‐related death (HR 0.12; p  < .001). The annual incidence of HCC treatment until tumour progression was 82.8% and 23.9% in the untreated and DAA‐treated groups, respectively (HR 0.30; p  < .001). DAA‐induced SVR significantly reduced the risk for tumour progression and liver‐related death and the frequency of HCC treatment following curative treatment for HCC at BCLC stage 0/A.